Longstanding suppurative granulomatous inflammation of the infratemporal fossa - Brian E. Kinard, DMD, MD; Kelly R. Magliocca, DMD, MPH; Jeannette Guarner, MD; Cecile A. Delille, MD, MSc; Steven M. Roser, DMD, MD (Oral and Maxillofacial Surgery Cases, 2016)
The purpose of this article is to present the clinical course, multidisciplinary management contributions, and outcome of a patient diagnosed with suppurative granulomatous inflammation in the posterior maxillary soft tissue region. A 50-year-old white male presented with a 5-year history of a gradually enlarging posterolateral left maxillary soft tissue mass and concomitant decrease in maximal incisal opening (MIO) to 4 mm. A firm, painless, nonmobile submucosal mass was palpable lateral to the left maxilla without drainage or lymphadenopathy. Computed tomography (CT) with contrast defined a 4 × 3 × 5 cm mildly enhancing mass in the left infratemporal fossa. The microscopic analysis was significant for several clusters of filamentous amphophilic material (suggesting sulfur granules) surrounded by granulomatous inflammation, including neutrophils. The morphologic appearance of the filamentous material in combination with the clinical presentation generated suspicion for Actinomyces; however, further workup was non-diagnostic. In efforts for definitive diagnosis, the specimen was directed to the CDC for 16S ribosomal RNA testing, which showed evidence of Strepococcus sanguinis and Campylobacter gracilis, known Actinomyces companion organisms. Empiric treatment for Actinomyces yielded clinical improvement. This case serves as a briefing for this form of uncommon inflammation and additionally serves to prime the reader on the distinction between actinomycosis, the clinical syndrome, and Actinomycosis, the bacteria. We present this case, perhaps from more of a philosophical standpoint, to illustrate the manner in which a longstanding, clinically significant, destructive process in an unusual anatomic location was successfully resolved via collaborative interdisciplinary management and months of effort.